2023
DOI: 10.1111/jdi.14088
|View full text |Cite
|
Sign up to set email alerts
|

Fermented soybean foods and diabetes

Yoshitaka Hashimoto,
Masahide Hamaguchi,
Michiaki Fukui

Abstract: The number of patients with type 2 diabetes mellitus is increasing, and its prevention and management are important. One of the factors contributing to the increased incidence of type 2 diabetes mellitus is the change in dietary habits, including a Westernized diet. Fermented foods are foods that are transformed by the action of microorganisms to produce beneficial effects in humans and have been consumed for thousands of years. The production and consumption of fermented soy foods, including natto, miso, douc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 125 publications
0
1
0
Order By: Relevance
“…After fermentation by microorganisms, some fermented soybean products have shown better anti‐hypertensive and antidiabetic effects (Hashimoto et al ., 2023; Liu et al ., 2022). It was found that soybean meal fermented by Bacillus subtilis significantly enhanced its inhibitory effect on angiotensin‐I‐converting enzyme, which is a powerful vasoconstrictor that causes elevated blood pressure (Lu et al ., 2022).…”
Section: Biological Activities Of Fermented Soybean Mealmentioning
confidence: 99%
“…After fermentation by microorganisms, some fermented soybean products have shown better anti‐hypertensive and antidiabetic effects (Hashimoto et al ., 2023; Liu et al ., 2022). It was found that soybean meal fermented by Bacillus subtilis significantly enhanced its inhibitory effect on angiotensin‐I‐converting enzyme, which is a powerful vasoconstrictor that causes elevated blood pressure (Lu et al ., 2022).…”
Section: Biological Activities Of Fermented Soybean Mealmentioning
confidence: 99%